KETERAMPILAN DRIBBLING DITINJAU DARI KEKUATAN OTOT TUNGKAI DAN KELINCAHAN PADA CABANG OLAHRAGA FUTSAL - Mustaqim, Ridha (Universitas Negeri Semarang, 2017)
The research aims to reveal correlation strength of limb muscles and agility with the skills of Dribbling in the futsal sport. It is poured into research issues, namely is a significant correlation between the strength of limb muscles with the skills of dribbling, whether there is a significant correlation between agility with the skills of dribbling, and whether there is a correlation between the strength of limb muscles may and agility together with dribbling skills in the sport of futsal. The methods used in this research is descriptive method, samples are used as many as 20 students SMAN 23 Bandung to following extra-curricular.The results of this research is, the correlation between the strength of the limb muscles and dribbling skills acquired t-count of 14.54, table larger than t = 2.10. Correlation between agility and dribbling skills t-count of 16.93 greater than t = table 2.10, while the correlation between the strength of the limb muscles and agility together obtained F calculate 36.82 greater than F 3.59 table.  Conclusion; The hypothesis States that there is a significant correlation between the strength of limb muscles with the skills of dribbling, dribbling skills and agility with jointly declared admissible